Medical Safety Legal Protection Based on Hospital Law in The Covid 19 Era - Yana Sylvana; St. Laksanto Utomo (CV. Publikasi Indonesia, 2021)
In Indonesia, the COVID-19 pandemic is entering a critical period. Health workers are a profession that is on the cutting edge of the fight against COVID-19. In these circumstances, health workers may have to put their lives on the line to safeguard the public from the development of the COVID-19 pandemic. The discussion's findings suggest that the legal protection of health workers' workplace safety as a result of the COVID-19 outbreak has not been properly applied, as required by law. During the COVID-19 pandemic, the rights of health professionals were still being ignored and not being met. As a result, the worldwide government's role and obligations are required to ensure that health professionals' rights as frontline responders to the spread of COVID-19 in Indonesia are respected. However, in fact, misunderstandings that lead to mediation are still common in the sphere of injustice, as are cases-certain bad cases 2 that could result in a repeat of events since there is no protective force or penalty that would prevent a person from behaving as a victim. In this study, the legal method adopted was normative legal research. The findings reveal that medical personnel's legal protection and right to safety have been regulated by legislation. These provisions, on the other hand, do not address the possible consequences of the COVID-19 virus spreading.